Effects of Liquid Metabolite Combinations from Lactobacillus Plantarums on Intestinal Microflora, Histology and Growth Performance of Piglets - Thu, Tran Van (2011)
Antibiotics has commonly used in piglets for growth promoter and diarrhoea prevention. However, excessive use of antibiotic may cause development of antibiotic resistance and residue in animal products. Application of lactic acid bacteria (LAB) has gained many beneficial effects on food preservation and animal gut health. The first experiment was conducted to select metabolite combinations produced from Lactobacillus plantarum by determination of pH, optical density (OD), Lactobacillus counts, organic acids and inhibitory activity test. The L. plantarum strains were TL1, RG11, RG14, RI11 and RS5. There are ten different combinations were established and each combination from 3 strains. The result of inhibitory test against Pediococcus acidilactici showed that Com 2 (TL1, RG11 and RI11), Com 5 (TL1, RG14 and RS5) and Com 7 (RG11, RG14 and RI11) were significantly more effective (P < 0.05) than the other 7 combinations. The Com 5 had the highest lactic acid concentration, whereas Com 5 and Com 7 had the highest acetic acid. Therefore, the Com 2, Com 5 and Com 7 were selected based on inhibitory activity and organic substances for further studies. The second experiment was carried out to investigate the effects of feeding different liquid metabolite combinations produced by L. plantarum on growth performance, diarrhoea incidence, pH, microflora counts and volatile fatty acids (VFA) in faeces and cholesterol, fatty acids in plasma and villi height, crypt depth in intestine of piglets. A total of 120 piglets were assigned into one of five treatments: 1) -ve control (antibiotic free); 2) +ve control (clortetracycline); 3) Com 1 (metabolite of TL1, RG11 and RI11 strains); 4) Com 2 (metabolite of TL1, RG14 and RS5 strains); 5) Com 3 (metabolite of RG11, RG14 and RI11 strains). The results showed that average daily gain (ADG) and feed conversion ratio (FCR) were improved significantly (P < 0.05) in metabolite combination groups. However, daily feed intake (DFI) was not significantly differences (P > 0.05) among the treatment groups. Diarrhoea incidence and faecal pH and Entrobacteriaceae (ENT) were reduced when piglets fed with Com 2 metabolites as compared to -ve control. Faecal LAB counts of metabolite groups were significantly higher (P < 0.05) than the groups without metabolites. Total faecal VFA and duodenum villi height of Com 2 were significantly higher (P < 0.05) than –ve control. No significant differences (P > 0.05) were found in intestinal crypt depth of piglets. Additionally, feeding of metabolite Com 2 reduced cholesterol and increased essential fatty acids in plasma of piglets. The third experiment investigated the effects of different metabolite concentrations on the growth performance, diarrhoea incidence, gut environment and nutrient digestibility in piglets. A total of 40 piglets were assigned into one of five treatments: 1) -ve control (free antibiotic); 2) +ve control (0.03% antibiotic of chlortetracycline); 3) Met 1 (0.1% metabolites); 4) Met 3 (0.3% metabolites); 5) Met 5 (0.5% metabolites). The results showed the piglets fed with Met 3 and Met 5 treatments were improved significantly (P < 0.05) for ADG and DFI as compared to –ve control. The diarrhoea incidence of piglets was reduced in Met 5 and +ve control groups. Moreover, feeding of 0.5% metabolites improved protein digestibility but did not improve energy utilization in piglets. There were significantly higher (P < 0.05) for digestial and faecal LAB counts in Met 3 and Met 5 treatments as compared to the other 3 treatments. In contrast, the pH and faecal ENT were significantly lower (P < 0.05) in Met 3 and Met 5 treatments. However, the highest total VFA observed in digesta was significant (P < 0.05) in Met 3 treatment. While, total VFA in faeces was significantly higher (P < 0.05) in Met 3 and Met 5 as compared to the other 3 treatments. These studies indicated that metabolite combinations produced by L. plantarum strains are potential alternative to antibiotics use as growth promoter in pigs. Feeding of 0.5% metabolite combination containing TL1, RG14 and RS5 strains demonstrated the best effect on the performances of piglets.